Influence Of Glycemic Control and Storage Conditions on Toothbrush Microbial Contamination Among Diabetic Patients (Journal of Dentistry and Allied Science, 2025)
Introduction: Toothbrushes can become contaminated with oral and environmental pathogens, posing infection risks. This study evaluates how glycemic control and toothbrush storage location jointly affect microbial contamination in diabetic patients. Methods: In this cross-sectional study (Rajshahi Medical College), 60 participants (30 diabetics, 30 non-diabetic controls) provided used toothbrushes (≥2 months old) and clinical data via questionnaire. Diabetic subjects were categorized by HbA1c: good (9%) glycemic control (10 per category). Each subject reported toothbrush storage (washroom [WR] vs. non-washroom [NWR]). Toothbrush heads were aseptically processed in sterile saline; aliquots were cultured on selective media (Blood Agar, MacConkey Agar, Sabouraud Dextrose Agar) to isolate bacteria and yeasts (e.g., Streptococcus mutans, Staphylococcus aureus, Escherichia coli, Pseudomonas spp., Candida). Statistical analysis (SPSS) used chi-square tests and Pearson correlation to assess associations, with p≤0.05 considered significant. Results: All toothbrushes (100%) were culture-positive, with S. mutans the most prevalent isolate. Contamination rates and species diversity were significantly higher in diabetics, especially with poor glycemic control . Poor-control diabetics showed elevated prevalence of S. aureus (~80%, p